Mobile Robot Path Following Controller Based On the Sirms Dynamically Connected Fuzzy Inference Model - Benmakhlouf, Abdeslam; Meraoumia, Abdellah; Louazene, Mohammed Lakhder (International Journal of Integrated Engineering, 2023)
This paper presents a simple and effective way to implement a path following controller for a differential drive wheeled mobile robot based on the single input rule modules (SIRMs) dynamically connected fuzzy inference model. The control of the mobile robot is divided into two control actions performed in parallel; the heading and the velocity controller. For the heading controller, each input item is assigned with a SIRM and a dynamic importance degree (DID). The velocity controller structure was modified to simplify the design and to fulfill the requirements of the path following method. Here, a common DID is used. The SIRMs and the dynamic importance degrees are designed such that the angular velocity control takes the highest priority over the linear velocity control of the mobile robot. By using the SIRMs and the dynamic importance degrees, the priority orders of the controls are automatically adjusted according to navigation situations. The proposed fuzzy controller has a simple and intuitively understandable structure, and executes the two control actions entirely in parallel. Simulation results show that the proposed fuzzy controller can drive a mobile robot smoothly with a high precision through a series of waypoints to attain its final target in short time.